Establishment of vestibular function multimodality platform. Issue 4 (April 2019) - Jheng, Ying-Chun; Yu, Chung-Huang; Chen, Po-Yin; Cheng, Yuan-Yang; Lin, Tai-Chi; Huang, Shih-En; Liu, Ding-Hao; Wang, Chien-Chih; Wei, Shun-Hwa; Kao, Chung-Lan
Abstract : Background: The technology of using inertial measurement units (IMUs) to detect motions in different body segments has drawn enormous attention to research and industry. In our previous research, we have applied IMUs in evaluating and treating patients with vestibular hypofunction. Furthermore, according to the research, when a person's head rotates over 60° on either side in the horizontal plane, and desires to focus vision on any targets, then the function of gaze shift comes in to operation. Herein, we aimed to use IMUs to build up a system to evaluate vestibular ocular reflex (VOR) during gaze shifting maneuver. Methods: In this study, we developed a platform, which combines the features of gaze shift and computerized dynamic visual acuity (cDVA), called the gaze shift DVA (gsDVA) platform. The gsDVA platform measures the orientations of the subject's head by IMU, and executed the evaluation according to the algorithm that was developed by us. Finally, we used the VICON system to validate the performance of gsDVA platform. Results: The performance of the accuracy was 2.41° ± 1.08°, the maximal sensor error was within 4.25°, and highly correlated between our platform and VICON ( p < 0.05, R = 0.99). The intraclass correlation coefficient (ICC) of between-day and within-day was 0.984 and 0.999, respectively. Furthermore, the platform not only executed the evaluation automatically but also recorded other information besides the head orientation, such as rotation speed, rotation time, reaction time, and visual acuity. Conclusion: In this study, we demonstrated the utility of vestibular evaluation, and this platform can help to clarify the relationship between gaze shift and VOR. This methodology is useful and can be applied efficiently to different disease groups for interactive evaluation and rehabilitation programs.